Clinical and Molecular Spectrum of Myotonia and Periodic Paralyses Associated With Mutations in SCN4A in a Large Cohort of Italian Patients - Maggi, Lorenzo; Brugnoni, Raffaella; Canioni, Eleonora; Tonin, Paola; Saletti, Veronica; Sola, Patrizia; Piccinelli, Stefano Cotti; Colleoni, Lara; Ferrigno, Paola; Pini, Antonella; Masson, Riccardo; Manganelli, Fiore; et al. (Frontiers in Neurology, 2020)
Background: Four main clinical phenotypes have been traditionally described in patients mutated in SCN4A, including sodium-channel myotonia (SCM), paramyotonia congenita (PMC), Hypokaliemic type II (HypoPP2) and Hyperkaliemic/Normokaliemic periodic paralysis (HyperPP/NormoPP); in addition, rare phenotypes associated with mutations in SCN4A are congenital myasthenic syndrome and congenital myopathy. However, only scarce data have been reported in literature on large patient cohorts including phenotypes characterized by myotonia and episodes of paralysis. Methods: We retrospectively investigated clinical and molecular features of 80 patients fulfilling the following criteria: 1) clinical and neurophysiological diagnosis of myotonia, or clinical diagnosis of PP, and 2) presence of a pathogenic SCN4A gene variant. Patients presenting at birth with episodic laryngospasm or congenital myopathy-like phenotype with later onset of myotonia were considered as neonatal SCN4A. Results: PMC was observed in 36 (45%) patients, SCM in 30 (37.5%), Hyper/NormoPP in 7 (8.7%), HypoPP2 in 3 (3.7%) and neonatal SCN4A in 4 (5%). The median age at onset was significantly earlier in PMC than in SCM (p < 0.01) and in Hyper/NormoPP than in HypoPP2 (p=0.02). Cold-induced myotonia was more frequently observed in PMC (n=34) than in SCM (n=23) (p=0.04). No significant difference was found in age at onset of episodes of paralysis among PMC and PP or in frequency of permanent weakness between PP (n=4), SCM (n=5) and PMC (n=10). PP was more frequently associated with mutations in the S4 region of the NaV1.4 channel protein compared to SCM and PMC (p<0.01); mutations causing PMC were concentrated in the C-terminal region of the protein, while SCM-associated mutations were detected in all the protein domains. Conclusions: Our data suggest that skeletal muscle channelopathies associated with mutations in SCN4A represent a continuum in the clinical spectrum.